2017
DOI: 10.1111/iej.12825
|View full text |Cite
|
Sign up to set email alerts
|

Apical stress distribution under vertical compaction of gutta‐percha and occlusal loads in canals with varying apical sizes: a three‐dimensional finite element analysis

Abstract: Apical enlargement caused stress distribution changes in the apical region of roots. The larger apical size led to higher stress concentration at the root apex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…A recent study showed that under vertical and lateral occlusal loads, greater apical enlargement resulted in increased stress on the remaining dentinal walls, especially at the apex. It also suggested that these areas would therefore be at an increased risk for crack formation during obturation (26). Overly aggressive canal preparation, such that the apical constriction is lost, may allow extrusion of irrigant solutions beyond the apex, which may cause breakthrough pain, mucosal and bone necrosis, sensory and motor defects, and may require hospitalization (27).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that under vertical and lateral occlusal loads, greater apical enlargement resulted in increased stress on the remaining dentinal walls, especially at the apex. It also suggested that these areas would therefore be at an increased risk for crack formation during obturation (26). Overly aggressive canal preparation, such that the apical constriction is lost, may allow extrusion of irrigant solutions beyond the apex, which may cause breakthrough pain, mucosal and bone necrosis, sensory and motor defects, and may require hospitalization (27).…”
Section: Discussionmentioning
confidence: 99%
“…Different simulated material properties (Young’s modulus (E) and Poisson’s ratio values) were generated, based on data from the literature (Table 2). 15,17,19 Cross-sections of root canal were created from the apex at intervals of 1.0 mm. To visualize the stress distributions and magnitudes in the models, the data were transformed into color graphics.…”
Section: Methodsmentioning
confidence: 99%
“…Two-direction (vertical and lateral) loading patterns were simulated with a 175-N force and applied to two 1-mm 2 areas. 17,18 The lateral load was applied to the lingual plane of the cusp at a 45° angle to the longitudinal axis of the mandibular premolar. Each part of the whole model was imported into the Abaqus software (Abaqus, V6.14, Dassault Simulia, Johnston, RI, USA) to perform static linear analysis.…”
Section: Methodsmentioning
confidence: 99%
“…21 Specifically in endodontics, this kind of analysis or finite element analysis (FEA) in general has been directed toward evaluation of fluid pattern during irrigation, physical parameters of dental instruments, tooth strength, etc. [22][23][24][25][26] One of the main advantages of CFD is the possibility of evaluating the entire irrigation process, without limiting to obtain a static image as it happens with microscopic or microbiological studies. 5,19 Furthermore, it also provides information about pressure and velocity distribution, which is difficult to obtain with in vitro and in vivo models.…”
Section: Introductionmentioning
confidence: 99%
“…CFD has already been used before to evaluate both circulatory and respiratory systems among others 21 . Specifically in endodontics, this kind of analysis or finite element analysis (FEA) in general has been directed toward evaluation of fluid pattern during irrigation, physical parameters of dental instruments, tooth strength, etc 22‐26 . One of the main advantages of CFD is the possibility of evaluating the entire irrigation process, without limiting to obtain a static image as it happens with microscopic or microbiological studies 5,19 .…”
Section: Introductionmentioning
confidence: 99%